Case report: Acute pericarditis following hepatic microwave ablation for liver metastasis - Pavon, Anna Giulia; Rubimbura, Vladimir; Nowacka, Anna; Hocquelet, Arnaud; Schwitter, Jurg; Rotzinger, David C. (Frontiers in Cardiovascular Medicine, 2023)
Hepatic microwave ablation (MWA) is a growing treatment modality in the field of primary and secondary liver cancer. One potential side effect is thermal damage to adjacent structures, including the pericardium if the hepatic lesion is located near the diaphragm. Hemorrhagic cardiac tamponade is known to be a rare but potentially life-threatening complication. Here we present the first case of cardiac complication following MWA treatment in a 55-year-old man who presented with late cardiac tamponade. Adequate and timely management is essential, and clinicians should be fully aware of the need to perform early transthoracic echocardiography to detect signs of pericardial effusion when cardiac involvement is suspected.